Smart Shoe Care: Enhancing Drying Efficiency and Material Preservation: Perawatan Cerdas Sepatu: Meningkatkan Efisiensi Pengeringan dan Preservasi Material - Dwi Hadidjaja; Akhmad Ahfas; Syamsudduha Syahrorini; Shazana Dhiya Ayuni (Academia Open, 2023)
This scientific article presents a novel approach to address the challenges of shoe drying by developing a controlled shoe drying system. The system utilizes a NodeMCU ESP8266 microcontroller with internet connectivity, enabling monitoring and control of the drying process via a smartphone application. By integrating temperature and humidity sensors, the system optimizes the drying time and prevents damage to shoe materials, thus ensuring the preservation of their quality. The research objectives were to enhance drying efficiency, reduce drying time, and maintain the integrity of shoe materials. Experimental methods involved the design and implementation of the system, followed by rigorous testing and evaluation. The results demonstrated significant improvements compared to conventional shoe dryers, reducing drying time from 1-2 days to an efficient duration. The implications of this research are profound, as the developed system offers a sustainable solution to shoe drying, contributing to the preservation of shoe materials and reducing wastage. The findings have relevance for the global footwear industry, with potential applications in shoe care services and consumer households alike. Highlights: Efficient shoe drying: The developed controlled system optimizes the drying process, reducing the drying time significantly compared to conventional methods. Material preservation: The integrated temperature and humidity control prevents damage to shoe materials, ensuring their quality and longevity. Smart technology application: The use of NodeMCU ESP8266 microcontroller with internet connectivity enables remote monitoring and control of the shoe drying system, enhancing convenience and accessibility. Keywords: Shoe drying, Controlled system, Temperature and humidity control, Material preservation, Smart technology.